Essentials of audiology : 290 illustrations - Gelfand, Stanley A., 1948- (New York : Thieme, 2016)
"This textbook attempts to provide a comprehensive overview of audiology at the introductory level; including such topics as acoustics, anatomy and physiology, sound perception, auditory disorders and the nature of hearing impairment, methods of measurement, screening, clinical assessment and clinical management. It is intended to serve as the core text for undergraduate students in speech, language and hearing, and might also serve the needs of beginning-level graduate students who need to learn or review the fundamentals of audiology. It is anticipated that the material will be covered in a one-, two- or three-term undergraduate sequence, depending on the organization of the communication sciences and disorders curriculum at a given college or university"--
Includes bibliographical references and indexes.
english
Keywords: Audiology